Modeling the Relationship Between Psychological Capital and Alexithymia with Emotional Divorce Through the Mediation of Spiritual Intelligence in Couples Seeking Divorce - Sabaghpour Sabzehmeidani, Hedieh; Azmoodeh, Masoumeh; Abdi, Reza; Panahali, Amir; Mesrabadi, Javad (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to determine the fit of the model examining the relationship between psychological capital and alexithymia with emotional divorce through the mediation of spiritual intelligence in couples seeking divorce. This research employed a descriptive-correlational design. The statistical population included all couples seeking divorce who referred to counseling centers in Babol in 2023 (N = 780). Using a simple random sampling method, 271 women were selected (n = 271) and responded to the following instruments: the Psychological Capital Questionnaire by Luthans et al. (2007), the Toronto Alexithymia Scale by Bagby et al. (1994), the Emotional Divorce Scale by Gottman et al. (1995), and the Spiritual Intelligence Questionnaire by Abdollahzadeh et al. (2008). Data were analyzed using structural equation modeling and path analysis. The findings revealed a significant negative correlation between psychological capital and emotional divorce (r = -0.476; p < .01), and a significant positive correlation between alexithymia and emotional divorce (r = 0.380; p < .01). Psychological capital had an indirect and negative effect on emotional divorce through the mediation of spiritual intelligence (β = -0.460; p < .01), and alexithymia had an indirect and negative effect on emotional divorce through the mediation of spiritual intelligence (β = -0.461; p < .01). The model of the relationship between psychological capital and alexithymia with emotional divorce mediated by spiritual intelligence demonstrated an adequate fit. From a theoretical perspective, this study contributes to the enrichment of psychological concepts and marital relationships. From a practical standpoint, it may serve as an effective tool for family counselors, couple therapists, and social policymakers to reduce emotional divorce and enhance the quality of family life.